Investigations of Theses on the History of Police Law Defended in the Russian Empire (in the Period of 1807 – 1917) - KLIMOV, Andrey Yurievich; TOKMACHYOVA, Anastasiya Yurievna; RYJOVA, Yulia Valerievna; ARTYOMOV, Viktor Mikhailovich; AFANASIEV, Vladimir Sergeevich (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
The purpose of the research is to compile a full catalog of theses on the history of police law defended at the law faculties of the universities of the Russian Empire from 1864 to 1917 and the issues studied in them. The article examines master's and doctoral theses on police law, defended at Kazan, Moscow, Kharkov, St. Petersburg, Kiev, Novorossiysk (in Odessa), and Tomsk Universities of the Russian Empire. The topics of the theses reflect separate units of the subject classifier of legal acts of the Russian Empire in the field of police law and elements of the nomenclature of the category of sciences ‘Police Law’. Research methods are: bibliographic search, bibliographic description, analysis, generalization, comparison, formal and logical, historical and legal, classification, structuring. The main results of the research are the following ones: the origins and evolution of the category of sciences ‘Police Law’ in the Russian Empire have been shown; the first master's thesis on police law defended within the category of ‘State Jurisprudence’ has been determined; a complete list of master's and doctoral theses, defended on police law in general, and on the history of police law in particular at the law faculties of the universities of the Russian Empire (except Derpt (Yuryev) University), which contains information on the authors, themes and structures of theses, questions and problems studied in them, on the dates and places of their defense, on the years of theses, on the dynamics of defense of theses on police law among universities and by years, has been made up; a complete list of candidate and doctoral theses, defended in the USSR and the Russian Federation on the history of police and police law in the Russian Empire, has been presented. The theoretical and practical significance of the research results is as follows: the research complements new scientific knowledge about the history of police law; the results of the research form the basis for the first database for the development of content and forms of new scientific results and new scientific achievements of the theses research on police law in the Russian Empire; the research allows improving the legislation on police in the Russian Federation.